Extracellular Vesicles After Allogeneic Hematopoietic Cell Transplantation: Emerging Role in Post-Transplant Complications - Lia, Giuseppe; Di Vito, Clara; Cerrano, Marco; Brunello, Lucia; Calcaterra, Francesca; Tapparo, Marta; Giaccone, Luisa; Mavilio, Domenico; Bruno, Benedetto (Frontiers in Immunology, 2020)
Extracellular Vesicles (EVs) play an important role in the cellular crosstalk by transferring bioactive molecules through biological barriers from a cell to another thus influencing recipient cell functions and phenotype. Therefore, EVs are increasingly being explored as biomarkers of disease progression or response to therapy and as potential therapeutic agents in different contexts including in hematological malignancies. Recently, an EV role has emerged in allogeneic hematopoietic cell transplantation (allo-HCT) as well. Allo-HCT often represents the only curative option in several hematological disorders but it is associated with potentially life-threatening complications that can have a significant impact on clinical outcomes. The most common complications have been well established and include graft-vs.-host disease (GvHD) and infections. Furthermore, relapse remains an important cause of treatment failure. The aim of this review is to summarize the current knowledge, the potential applications and clinical relevance of EVs in allo-HCT. Herein, we will mainly focus on the immune-modulating properties of EVs, in particular those derived from Mesenchymal stromal cells, as potential therapeutic strategy to improve allo-HCT outcome. Moreover, we will briefly describe the main findings on EVs as biomarkers to monitor GvHD onset and tumor relapse.